2006
DOI: 10.1080/17470210600750558
|View full text |Cite
|
Sign up to set email alerts
|

Does word frequency affect lexical selection in speech production?

Abstract: We evaluated whether lexical selection in speech production is affected by word frequency by means of two experiments. In Experiment 1 participants named pictures using utterances with the structure "pronoun + verb + adjective". In Experiment 2 participants had to perform a gender decision task on the same pictures. Access to the noun's grammatical gender is needed in both tasks, and therefore lexical selection (lemma retrieval) is required. However, retrieval of the phonological properties (lexeme retrieval) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
57
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 21 publications
13
57
0
2
Order By: Relevance
“…Because some studies of monolingual picture naming showed that frequency effects become smaller with repetition (Griffin & Bock, 1998;Oldfield & Wingfield, 1965; for similar results see Forster & Davis, 1984; Scarborough et al, 1977), this study supports the weaker links account by suggesting that repetition gives bilinguals a chance to "catch up" to monolinguals in terms of degree of use. However, it is not clear to what extent repetition in the context of an experiment is analogous to increased use over time (Griffin, 2002;Murray & Forster, 2004; see discussion in Gollan, Montoya, et al, 2005), and some have found frequency effects to be remarkably stable in magnitude over several or many repetitions (Levelt, Roelofs, & Meyer, 1999;Navarrete, Basagni, Alario, & Costa, 2006).A more direct test of the weaker links hypothesis can be obtained by directly manipulating word-frequency in the bilingual to monolingual comparison. To explain frequency effects, many models of language production (e.g., Caramazza, 1997;Dell, 1986, 1990, Dell et al, 1997Griffin & Bock, 1998;Levelt, et al, 1999), and models of language comprehension whether monolingual (e.g., McClelland & Rumelhart, 1981;Morton, 1970;Plaut, McClelland, Seidenberg, & Patterson, 1996;Seidenberg & McClelland, 1990) or bilingual (Dijkstra & Van Heuven, 2002), make the following, or very similar, assumptions: (a) lexical representations accumulate baseline levels of activation with increased use, (b) baseline levels of activation are promoted upwards with increased use as a proportion of their distance from threshold, (c) selection occurs when activation levels reach threshold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because some studies of monolingual picture naming showed that frequency effects become smaller with repetition (Griffin & Bock, 1998;Oldfield & Wingfield, 1965; for similar results see Forster & Davis, 1984; Scarborough et al, 1977), this study supports the weaker links account by suggesting that repetition gives bilinguals a chance to "catch up" to monolinguals in terms of degree of use. However, it is not clear to what extent repetition in the context of an experiment is analogous to increased use over time (Griffin, 2002;Murray & Forster, 2004; see discussion in Gollan, Montoya, et al, 2005), and some have found frequency effects to be remarkably stable in magnitude over several or many repetitions (Levelt, Roelofs, & Meyer, 1999;Navarrete, Basagni, Alario, & Costa, 2006).A more direct test of the weaker links hypothesis can be obtained by directly manipulating word-frequency in the bilingual to monolingual comparison. To explain frequency effects, many models of language production (e.g., Caramazza, 1997;Dell, 1986, 1990, Dell et al, 1997Griffin & Bock, 1998;Levelt, et al, 1999), and models of language comprehension whether monolingual (e.g., McClelland & Rumelhart, 1981;Morton, 1970;Plaut, McClelland, Seidenberg, & Patterson, 1996;Seidenberg & McClelland, 1990) or bilingual (Dijkstra & Van Heuven, 2002), make the following, or very similar, assumptions: (a) lexical representations accumulate baseline levels of activation with increased use, (b) baseline levels of activation are promoted upwards with increased use as a proportion of their distance from threshold, (c) selection occurs when activation levels reach threshold.…”
mentioning
confidence: 99%
“…Because some studies of monolingual picture naming showed that frequency effects become smaller with repetition (Griffin & Bock, 1998;Oldfield & Wingfield, 1965; for similar results see Forster & Davis, 1984;Scarborough et al, 1977), this study supports the weaker links account by suggesting that repetition gives bilinguals a chance to "catch up" to monolinguals in terms of degree of use. However, it is not clear to what extent repetition in the context of an experiment is analogous to increased use over time (Griffin, 2002;Murray & Forster, 2004; see discussion in , and some have found frequency effects to be remarkably stable in magnitude over several or many repetitions (Levelt, Roelofs, & Meyer, 1999;Navarrete, Basagni, Alario, & Costa, 2006).…”
mentioning
confidence: 99%
“…In the first case, during the delay participants were biased to process pictures up to the semantic level. In contrast, when the prevalent task was gender decision, grammatical-gender information stored with the lexical representation of the target pictures had to be accessed (e.g., Navarrete, Basagni, Alario, & Costa, 2006), and therefore, during the delay participants were biased to process pictures up to that level.…”
mentioning
confidence: 99%
“…Pesquisas indicam que palavras de alta freqüência tendem a ser reconhecidas mais rapidamente e identificadas com maior precisão do que as palavras de baixa freqüência. Da mesma forma, as palavras de alta freqüência são produzidas mais rapidamente e são menos sujeitas a erros (GERMAN; NEWMAN, 2004;NAVARRETE et al, 2006).…”
Section: Variações Individuais E Tendências Na Aquisição Lexicalunclassified
“…De maneira geral, quanto mais "concreta" uma palavra, maior a facilidade de ser adquirida (BLOOM, 2001;CAMARATA;EYER et al, 2002), contanto que a criança seja suficientemente exposta a ela (GERMAN; NEWMAN, 2004;NAVARRETE et al, 2006). Além disso, a possibilidade de manipular e observar as ações possíveis (para as crianças do G2) GELMAN, 1976;LEONARD et al, 1982) e podem ser justificados pelos estudos sobre mapeamento rápido e acesso lexical (CAPONE; MCGREGOR, 2005;DOLLAGHAN, 1987;HAHN, 2007;GRAY, 2003).…”
Section: Etapa I -Exposiçãounclassified